2018
DOI: 10.3389/fpls.2018.00120
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and Linkage of Virulence Genes in Chinese Predominant Race CYR32 of the Wheat Stripe Rust Pathogen Puccinia striiformis f. sp. tritici

Abstract: Puccinia striiformis f.sp. tritici (Pst) is the causal agent of stripe (yellow) rust on wheat. It seriously threatens wheat production worldwide. The obligate biotrophic fungus is highly capable of producing new virulent races that can overcome resistance. Studying the inheritance of Pst virulence using the classical genetic approach was not possible until the recent discovery of its sexual stage on barberry plants. In the present study, 127 progeny isolates were obtained by selfing a representative Chinese Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 40 publications
6
45
3
Order By: Relevance
“…By testing the parental and progeny isolates on 24 wheat Yr single-gene lines, the parental isolate was found to be homozygous for its avirulence phenotypes to Yr5, Yr10, Yr15, Yr24, Yr32, YrSp, YrTr1, YrTye, YrExp2, and Yr26; homozygous for its virulence phenotypes to Yr1, Yr2, Yr3, Yr6, Yr7, Yr8, Yr9, Yr17, Yr25, Yr27, Yr28, YrA, Yr32, and Yr47; and heterozygous for its VPs to Yr1, Yr2, Yr9, Yr17, Yr47, YrA, YrSp, YrTr1, YrExp2, and Yr47. Heterozygosity and homozygosity of avirulence/virulence phenotypes have been reported using selfed populations of PST isolates of Chinese races [27,28], a US race of PST [41], and a Chinese predominant race CYR32 of PST [7]. We found that both Yr5 and Yr15 genes were resistant against all the progeny isolates and the parental isolate, indicating their effectiveness in China and Pakistan, which correlates with previous studies [7,27,28,41].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…By testing the parental and progeny isolates on 24 wheat Yr single-gene lines, the parental isolate was found to be homozygous for its avirulence phenotypes to Yr5, Yr10, Yr15, Yr24, Yr32, YrSp, YrTr1, YrTye, YrExp2, and Yr26; homozygous for its virulence phenotypes to Yr1, Yr2, Yr3, Yr6, Yr7, Yr8, Yr9, Yr17, Yr25, Yr27, Yr28, YrA, Yr32, and Yr47; and heterozygous for its VPs to Yr1, Yr2, Yr9, Yr17, Yr47, YrA, YrSp, YrTr1, YrExp2, and Yr47. Heterozygosity and homozygosity of avirulence/virulence phenotypes have been reported using selfed populations of PST isolates of Chinese races [27,28], a US race of PST [41], and a Chinese predominant race CYR32 of PST [7]. We found that both Yr5 and Yr15 genes were resistant against all the progeny isolates and the parental isolate, indicating their effectiveness in China and Pakistan, which correlates with previous studies [7,27,28,41].…”
Section: Discussionsupporting
confidence: 90%
“…The segregation of avirulence/virulence phenotypes on 10 Yr single-gene lines determined that the VPs to YrSp, YrTr1, and Yr47 were controlled by a single locus; those on six Yr single-gene lines (Yr1, Yr2, Yr9, Yr17, Yr27, and YrA were controlled by two loci. Both single-locus and two loci have been reported in previous studies [7,27,28,41]. Tian et al [27] reported one locus controlling virulence phenotypes to YrSp, which is similar in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations